Perlindungan Hukum terhadap Perawat pada Rumah Sakit Berdasarkan Undang-Undang Nomor 38 Tahun 2014 tentang Keperawatan - R.H. Riasari (Jurnal Hukum Lex Generalis, 2021)
This paper discusses the legal protection of nurses in hospitals based on law number 38 of 2014. The type of research used in this research is normative research, namely research that examines document studies, namely using various secondary data as normative research. The results of this journal show that nurses who receive delegations or mandates in carrying out medical tasks are more careful and continue to communicate with doctors who delegate these tasks so that malpractice does not occur. In addition, so that nurses do not accept demands both from the aspect of speech, civil and administrative aspects, it is better if the delegation of tasks is in the form of written documents.